Mongolia - Public Expenditure and Financial Management Review : Bridging the Public Expenditure Management Gap - World Bank (Washington, DC, 2013)
Mongolia has realized important progress toward more efficient and sustainable public finances over the last decade. However, weaknesses in the institutional and structural reform agenda threaten Mongolia's fiscal balances. The government proposes to grow at 6 percent. This report discusses policy measures needed to ensure success of government programs. Following the introduction, chapter 2 discusses past performance and provides a brief discussion of recent economic and social developments. Chapter 3 discusses future challenges, analyzes the main sources of fiscal pressure on Mongolia's budget, and proposes a sustainable macroeconomic reform path. Chapter 4 evaluates budget execution processes. Chapter 5 discusses the impact of intergovernmental fiscal relations on fiscal balances, and service delivery. Chapter 6 discusses governance. Chapter 7 analyzes budget formulation and policy coordination processes. Chapter 8 discuses public sector resource allocations, with particular emphasis on education, health, and the environment sectors. The report concludes by discussing the importance of putting into place measures to bridge the gap between existing public expenditure management practices and those needed to improve the overall performance of the Mongolian public sector, and proposes a framework within which this can be achieved.